False remembering in real life: James Ost's contributions to memory psychology. Issue 6 (3rd July 2022) - Blank, Hartmut; Nash, Robert A.; Otgaar, Henry; Patihis, Lawrence; Rubínová, Eva
ABSTRACT: This special issue honours James Ost's (1973–2019) contributions to our understanding of false and distorted remembering. In our editorial, we introduce some of James' distinctive research themes including the experiences of people who retract "recovered" memories, social (e.g., co-witness and interviewer influence) and personality influences on false remembering, the nature of false remembering itself (e.g., different types of false memories; false memories vs. false beliefs), public understanding of (false) memory, and a historical link to the work of Frederic Bartlett. We illustrate these themes through a number of key publications. The unifying thread behind James' work is his core interest in false/distorted remembering in real-life (typically high-stake) situations, in line with his engagement with the British False Memory Society and his role as an expert witness in court trials. The articles included in this special issue elaborate on the research themes to which James devoted his career and his curiosity.